Helicopter Parenting and the Moderating Impact of Gender for University Students with ADHD. Issue 1 (2nd January 2020) - Buchanan, Tom; LeMoyne, Terri
ABSTRACT: The intersection of helicopter parenting, gender, and Attention Deficit Hyperactivity Disorder (ADHD) is examined. Existing research on helicopter parenting focuses on negative consequences. Using a sample of students at a university in the mid southern United States ( N = 287), we find that that helicopter parenting is negatively related to self-efficacy, but not for males with ADHD. For university students self-reporting a diagnosis of ADHD, the impact of helicopter parenting on self-efficacy depends on gender. This is an intriguing finding given previous research finding predominantly negative consequences. It informs us of both the salience of gender socialisation as well as the importance of understanding of the different ways ADHD occurs in young women compared to men. This information is important for parents as well as university administrators in relation to the growing concern for parental involvement in students' affairs. Existing research suggests women experiencing ADHD are more likely to exhibit inattentiveness while men exhibit hyperactivity more often. Universities and involved parents could learn more about the particular ADHD subtypes among their diagnosed students and children. This knowledge would likely lead to more effective, independence provoking parenting and accommodations as students experiencing ADHD enter universities, particularly for women.